Boldness Predicts Aggressiveness, Metabolism, and Activity in Black Rockfish Sebastes schlegelii - Fu, Yiqiu; Zhang, Zonghang; Zhang, Zhen; Shen, Fengyuan; Xu, Xiuwen; Li, Zheng; Zhang, Yanhao; Zhang, Xiumei (Frontiers in Marine Science, 2021)
Animal personality refers to individual behavioral and physiological differences that are consistent over time and across context. Recently, the fish personality has gained increasing attention, especially from the perspective of aquaculture production. Here, we used an important aquaculture species, black rockfish Sebastes schlegelii, as the target animal, and conducted a series of experiments to explore the relationships among fish boldness, aggressiveness, locomotor activity, opercular beat rate, standard metabolic rate, and cortisol level. Generally, the results showed that the boldness of black rockfish was significantly, positively correlated with fish aggressiveness, stressed locomotor activity, and standard metabolic rate, while was negatively correlated with stressed opercular beat rate. Bold fish had significantly higher aggressiveness, standard metabolic rate, and stressed locomotor activity but lower stressed opercular beat rate. However, there were no significant correlations between boldness and basal locomotor activity or between boldness and basal cortisol level. These results preliminarily constructed the behavioral and physiological spectrum of black rockfish in the context of fish personality and clearly indicated that the boldness could be used as a discrimination tool to predict fish aggressiveness and metabolic rate, which may have valuable applications for decreasing fish harmful aggression and increasing fish welfare in the aquaculture industry.